Journal of the American College of Cardiology
Features the online edition of the "Journal of the American College of Cardiology" (JACC), published by Elsevier Science Inc. Posts a "Journal" overview, the current month's table of contents, job listings, sample abstracts from recent issues, and a directory of related periodicals on the WWW. Provides access to home pages of "JACC" advertisers and the American College of Cardiology.